The Importance of Information Technologies in Protecting the Young Generation From Information Attacks in the Process of Globalization - Halimjonov Ulug`bek Nasirjon ugli (Miasto Przyszłości, 2024)
In this article, the importance of information technologies in protecting the young generation from information attacks, the effective use of information technologies by the young generation, the culture of using information technologies, globalization processes and information security, the development of scientific potential, and the practical skills necessary to protect the young generation from the threats faced by the use of information technologies. A lot of information has been given about the role of the Internet and the culture of using it, promoting their development in line with the processes of globalization and gaining their place.